INCLUDERE: A Mobile-VR Demo for Inclusive, Empathy-Oriented Storytelling - Peres, Tati; Peres, Fabiana F. F.; Nunes, Fatima L. S.; Teixeira, Joao Marcelo (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
INCLUDERE is a six-minute, culturally grounded mobile-VR experience that invites visitors to inhabit—rather than merely observe—the spatial, sensory, and social frictions shaping disabled life in Brazil. The journey unfolds through six metaphor-driven vignettes (autism, dwarfism, visual, motor and hearing impairments, plus an intersectional finale), each pairing a tailored interaction mechanic with stylised volumetric live-action footage running in real time on Meta Quest headsets.